Estrutura da metacomunidade de peixes em riachos urbanizados na Bacia do Rio Sorocaba - Silva, Guilherme Raphael Camargo Arcanjo (Universidade Federal de São Carlos, 2026)
Urbanization acts as a restrictive environmental filter that disrupts aquatic biodiversity through the "Urban Stream Syndrome." This study investigated the fish metacommunity structure in 18 urban streams in Sorocaba, SE Brazil, to determine whether community assembly is driven by environmental selection (species sorting) or spatial processes. We applied the Elements of Metacommunity Structure (EEM) framework, beta diversity decomposition (Baselga and Podani methods), and Asymmetric Eigenvector Maps (AEM) to model directional dispersal. A total of 2,246 individuals from 18 species were collected. EEM analysis revealed a Quasi-Clementsian pattern, characterized by significant positive coherence and high boundary clumping, indicating that species groups replace one another along a latent gradient of Physical Habitat Index (PHI). Beta diversity decomposition via the Podani method showed that richness difference (59.2%) outweighed replacement (40.7%), signaling a severe nestedness-like faunal impoverishment. Partial Redundancy Analysis (pRDA) confirmed that the environmental fraction (PHI) significantly explained community variation, while the pure spatial component (AEM) was non-significant. These results demonstrate that local habitat degradation specifically loss of canopy cover and substrate homogenization overrides regional dispersal in shaping urban fish assemblages. Sensitive species are eliminated without replacement by specialists, leaving "niche vacancies" occupied by tolerant generalists like Phalloceros harpagos. Conservation efforts must prioritize the restoration of riparian zones and instream morphological complexity over simple hydrological connectivity to mitigate biotic homogenization in tropical urban landscapes.
Metacommunity structure of stream fish assemblages in urbanized catchments of the Sorocaba River Basin
Keywords: Metacomunidade; Quasi-Estrutura Clementsiana; Peixes de riachos urbanos; Metacommunity; Clementsian Quasi-Structure; Stream fishes; Peixes de riachos urbanos; CIENCIAS BIOLOGICAS::ECOLOGIA; 14. Vida na Água